BEYOND THE COUNCIL. ON LOCAL ELITE THROUGH THE EXAMPLE OF THE CHINCHILLA TOWNHOUSE IN THE 17TH CENTURY - Molina Puche, Sebastián (Revista de Historia Social y de las Mentalidades, 2011)
In this article, after offering a critical relation of the recent works more remarkable than  have been centered in the oligarchies study and loc al elite of the different Spanish regions  in the Early Modern Age, we tried to show which are the “dangers” to make an historical  analysis in which is confused to the members of the city council oligarchy with the  members of the authentic leader group of a locality , a frequent relative error in the Spanish  modernism.
Keywords: Oligarchy; power elite; municipal council